2020
DOI: 10.3390/nu12020462
|View full text |Cite
|
Sign up to set email alerts
|

Association between the Degree of Processing of Consumed Foods and Sleep Quality in Adolescents

Abstract: The aim of this study was to evaluate the association between food consumption by the degree of processing and sleep quality in adolescents from São Luís, Maranhão, Brazil. A cross-sectional study with 2499 adolescents (aged 18 to 19 years) was developed. Exposure variables included energy contributions of food groups stratified by the NOVA classification: fresh or minimally processed foods (FMPF), processed foods (PF), and ultra-processed foods (UPF), categorized into quartiles. The outcome variable was sleep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 48 publications
(62 reference statements)
4
22
0
2
Order By: Relevance
“…Our findings concerning enhancements in resting habits are also consistent with studies showing improvements in the number of hours of sleep and sleep quality after eight weeks of mindfulness training, including flow meditation [35,59] This is a relevant finding since insufficient rest due to bad sleeping habits is related to poor academic performance [13].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings concerning enhancements in resting habits are also consistent with studies showing improvements in the number of hours of sleep and sleep quality after eight weeks of mindfulness training, including flow meditation [35,59] This is a relevant finding since insufficient rest due to bad sleeping habits is related to poor academic performance [13].…”
Section: Discussionsupporting
confidence: 90%
“…Poor sleep quality is a recurrent feature of student life and affects not only cognitive processes, but also recovery from stress and the elimination of fatigue, increasing the possibility of poor school performance [10]. Moreover, several studies have shown that sleeping problems, including bad resting habits, correlate positively with both uncontrolled and emotional eating in differing populations [9,11,12] By contrast, sleep duration and sleep quality have been associated with healthy diets [13].…”
Section: Introductionmentioning
confidence: 99%
“…Our findings concerning enhancements in rest habits are also consistent with studies showing improvements in the number of hours of sleep and sleep quality after eight weeks of mindfulness training including flow meditation [34,58]. This is a relevant finding since insufficient rest due to bad sleeping habits is related to poor academic performance [2].…”
Section: Discussionsupporting
confidence: 90%
“…In Spain, these students are distancing themselves from the traditional Mediterranean diet and food patterns [1]. Lifestyle changes of the past few decades have increasingly led to changes in eating habits such as the reduced consumption of fresh or minimally processed foods and increased consumption of ultra-processed products [2]. New eating habits are reflected in an unhealthy diet and various health-related problems including being overweight [1,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation